2002
DOI: 10.1007/s00264-002-0356-2
|View full text |Cite
|
Sign up to set email alerts
|

Cemented or uncemented hemiarthroplasty for displaced intracapsular femoral neck fractures

Abstract: The aim of this study was to establish whether or not to cement the hemiarthroplasty for displaced intracapsular femoral neck fractures in the elderly. Consecutive patients treated by hemiarthroplasty in adjacent hospitals were reviewed. The same monoblock prosthesis was used; in hospital A they were uncemented (121 patients), and in hospital B they were cemented (123 patients). Notes were reviewed retrospectively. Surviving patients (50 and 56 respectively) were assessed prospectively for pain and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 21 publications
4
62
0
1
Order By: Relevance
“…Our series of patients in both the groups is in no exception to the fact that the fractures of the neck of femur are more common in elderly population as the mean age of our study subjects was more than 70 years and the global epidemiology also admit this fact. Khan et al [7] and Santini et al [13] also noted the same scenario among our Indian subjects. Female preponderance in our study is mainly due to the fact that osteoporosis is one of the main risk factor for fracture neck of femur, which is more common in females.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our series of patients in both the groups is in no exception to the fact that the fractures of the neck of femur are more common in elderly population as the mean age of our study subjects was more than 70 years and the global epidemiology also admit this fact. Khan et al [7] and Santini et al [13] also noted the same scenario among our Indian subjects. Female preponderance in our study is mainly due to the fact that osteoporosis is one of the main risk factor for fracture neck of femur, which is more common in females.…”
Section: Discussionsupporting
confidence: 85%
“…There is some evidence of inferior short-term results, with decreased mobility and more pain when using an uncemented implant, and concerns regarding fixation problems with uncemented stems in osteoporotic bone have been raised. This may be the result of the inferior method of fixation or the design of the prosthesis [7,8] . The recent introduction of modular hemiarthroplasty for hip fractures had led to a number of prospective trials comparing cemented and uncemented hemiarthroplasty and had shown a very similar results for both the procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Where as in some studies like M. I. Parker [8] , et al concluded that degree of residual pain was less in those treated with a cemented prosthesis (p<0.0001) three months after surgery. R.J. Khan [9] et al, by prospective assessment revealed a highly statistically significant greater deterioration in pain (P=0.003), walking ability (P=0.002), use of walking aids (P=0.004) and activities of daily living (P=0.009) in the uncemented group The results in our study did not show any statistical difference in the evaluation of limp (P= 0.088), ability to walk (P = 0.439) and use of walking aids (P = 0.270) which matches with other similar studies like Jaimo Ahn, Li-Xing Man [6] , et al ; Wender Figved [5] , et al ; Hansen [7] , et al Whereas R.J. Khan [9] , et al by prospective assessment revealed a highly statistically significant greater deterioration in pain (P=0.003), walking ability (P=0.002), use of walking aids (P=0.004) and activities of daily living (P=0.009) in the uncemented group. In the uncemented group 4 patients (20%) had excellent results; 14 patients (70%) had good results and 2 patients (10%) had fair results with the mean Harris hip score of 85; whereas in the cemented group 3 patients (15.79%) had excellent results; 10 patients (52.63%) had good results; 5 patients (26.32%) had fair results and one patient (5.26%) had poor functional result, with the mean Harris hip score of 81.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the result of the inferior method of fixation or the design of the prosthesis [21,29]. One randomized comparison of an hydroxyapatite (HA)-coated implant and a conventional uncemented implant showed better functional results with the HA-coated prosthesis [25], and we are unaware of any randomized trials comparing hemiarthroplasties using uncemented HA-coated implants with cemented implants for treatment of femoral neck fractures.…”
Section: Introductionmentioning
confidence: 99%